1985
DOI: 10.1007/bf00544065
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of infusion regimens for thiopentone as a primary anaesthetic agent

Abstract: Several multi-stage infusion regimens and a computer controlled exponentially decreasing infusion regimen were evaluated in twelve patients undergoing head and neck surgery or neurosurgery. Thiopentone dosage was based on the mean of pharmacokinetic parameter values from the literature and adjusted for each patient's lean body mass in order to rapidly achieve a predetermined plasma thiopentone concentration of 15 or 20 micrograms/ml in the period following the initial bolus dose to induce anaesthesia. Anaesthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1987
1987
2010
2010

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…The intensity of effect corresponds to the 20-30 % increase in the MAC of halothane found in rabbits with similar plasma concentrations of laudanosine [7]. Using opening of eyes on command as a criterion, awakening from anaesthesia has previously been found to occur at a relatively constant alveolar concentration for several of the volatile anaesthetic agents [15] and of thiopentone following infusion anaesthesia [16]. Eye opening on command may be considered an all-or-none response and does not require a blind observer for accurate assessment.…”
Section: Discussionmentioning
confidence: 96%
“…The intensity of effect corresponds to the 20-30 % increase in the MAC of halothane found in rabbits with similar plasma concentrations of laudanosine [7]. Using opening of eyes on command as a criterion, awakening from anaesthesia has previously been found to occur at a relatively constant alveolar concentration for several of the volatile anaesthetic agents [15] and of thiopentone following infusion anaesthesia [16]. Eye opening on command may be considered an all-or-none response and does not require a blind observer for accurate assessment.…”
Section: Discussionmentioning
confidence: 96%
“…A variable-rate infusion of pethidine, targeting a plasma concentration of 400 ng/ml, was then started. The infusion profile was based on a modification of the method of Kruger-Thiemer 25 and published data 26 . The pethidine infusion continued until induction of general anaesthesia.…”
Section: Methodsmentioning
confidence: 99%
“…Crankshaw et al (1985) showed that at the time of surgery thiopentone concentrations can be predicted quite accurately because total plasma clearance strongly correlates with lean body mass. A mean elimination half-life of 15 ± 7.32 hours was calculated, which is slightly longer than following single injections.…”
Section: Modelling Of Thiopentone Kineticsmentioning
confidence: 98%